KEMAMPUAN MEMAHAMI WACANA ARGUMENTASI SISWA KELAS VIII SMP NEGERI 9 PEKANBARU - Ningsih, Herni Oktavia; Hakim, H. Nursal; Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study examines the ability to understand the discourse argumentation class VIII SMP Negeri 9 Pekanbaru. This study aimed to obtain information that will be described on the ability to understand the discourse argumentation. Understand the arguments of the dircourse aspect is the main idea and the idea of the explanatory. This research is descriptive quantitative research. This research data is test data discourse argumentation class VIII SMP Negeri 9 Pekanbaru aspects of the main idea and the idea of the explanatory. Instrument in this study is the text of discourse argument with two titles discourse which contains 29 multiple choice questions, 8 and 21 about the main idea about ideas descriptors. The data collection was done by using the test. Population in this study were 324 students with the determination of a sample of 180 students. Data were analyzed with descriptive methods. Validity of the data obtained through the method of data validation. Results of this study of the test result the ability to understand the discourse argumentation class VIII SMP Negeri 9 Pekanbaru. Seen from the aspect of understanding the main idea in discourse 1 and discourse 2 gained an average value amounted to 77,99 with the medium category. Then, from the aspect of the idea of explanatory discourse 1 and 2 was value obtained by an average of 57,17 with a low category.Keyword: discourse argumentation, the main idea, the idea explanatory.